Bidentate NHC^pyrozolate ligands in luminescent platinum(ii) complexes1. Issue 18 (14th May 2015) - Naziruddin, Abbas Raja; Galstyan, Anzhela; Iordache, Adriana; Daniliuc, Constantin G.; Strassert, Cristian A.; De Cola, Luisa
<x xml:space="preserve">Abstract</x> The tuning of luminescence from blue to yellow was achieved with platinum complexes containing NHC^pyrozolate and functionalized-phenyl-pyridine or triazole-pyridine ligands.